1991
DOI: 10.1159/000174759
|View full text |Cite
|
Sign up to set email alerts
|

Heart Disease in Native Americans

Abstract: Cardiovascular disease is one of the major causes of death among native Americans. Ischemic heart disease has been relatively uncommon in the past, but this entity is rapidly becoming more frequent among Indians as a result of Western acculturation (Western high-fat diet, smoking, sedentary lifestyle). Hypertension remains a major problem in native American populations. Hypertension is often inadequately detected and treated in Indians. Rheumatic fever and rheumatic heart disease are moderately common and appa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Native North Americans have traditionally been thought to have a low prevalence of IHD. Mortality from IHD among Native Americans was lower than that among the general US population in 1984, 4 and studies of several Native Canadian groups have demonstrated IHD rates that are lower than those of a comparable broad population. 5,6 However, Native populations have undergone significant social, economic, and cultural changes in the past several decades, some of which would be anticipated to have negatively affected the health status of Native North Americans.…”
mentioning
confidence: 94%
“…Native North Americans have traditionally been thought to have a low prevalence of IHD. Mortality from IHD among Native Americans was lower than that among the general US population in 1984, 4 and studies of several Native Canadian groups have demonstrated IHD rates that are lower than those of a comparable broad population. 5,6 However, Native populations have undergone significant social, economic, and cultural changes in the past several decades, some of which would be anticipated to have negatively affected the health status of Native North Americans.…”
mentioning
confidence: 94%
“…Today, there is a growing need for disease risk factor data for various chronic diseases among Native American population as health conditions have shifted from a high prevalence of infectious diseases to a higher chronic disease burden (Giuliano, Papenfuss, Guernsey De Zapien, Tilousi, & Nuvayestewa, 1998). Native Americans had a very low prevalence of CVD in the past (Alpert, Goldberg, Ockene, & Taylor, 1991; Galloway, 2004; National Institute of Health [NIH], 2001). A common idea shared by researchers and clinicians was that Native Americans had some inherent protection against CVD (NIH).…”
Section: Introductionmentioning
confidence: 99%
“…Poorer outcomes in Native Americans following CABG are most likely due to multiple factors. One potential cause for the rising incidence of cardiovascular disease in American Indians is the increasing prevalence of important cardiovascular risk factors due to gradual acculturation of Western diets and lifestyles 14 . Diabetes mellitus, in particular, is highly prevalent in several Native American tribes 15 and because diabetes may confer increased risk for death following CABG, 16,17 this might explain, at least in part, our findings of increased in‐hospital mortality from CABG among Native Americans.…”
Section: Discussionmentioning
confidence: 93%